Paying for payments: free payments and optimal interchange fees - Søren Korsgaard (European Central Bank (ECB), 2014)
Do consumers and merchants use the most efficient payment instruments? I examine how inter- change fees, which are fees paid from merchants' banks to consumers' banks when card transactions take place, influence the choice between cash and payment cards. I show that when consumers do not pay transaction fees to banks - a common feature in bank contracts - card use is declining in interchange fees, and surcharging does not neutralize interchange fees. According to my model, banks set interchange fees at too high a level, resulting in too few card payments. I derive an optimal interchange fee which depends only on the relative costs of producing cash and card payments and can be used by regulators to assess privately set interchange fees. When calibrated to cost data, the model implies an optimal fee that is low and may even be negative. The findings are consistent with empirical evidence of high card usage in countries with no interchange fees and have implications for the regulation of interchange fees.
Keywords: E42; G21; G28; 330; financial regulation; interchange fees; payments